2021
DOI: 10.34133/2021/9759016
|View full text |Cite
|
Sign up to set email alerts
|

Social and Behavioral Determinants of Health in the Era of Artificial Intelligence with Electronic Health Records: A Scoping Review

Abstract: Background. There is growing evidence that social and behavioral determinants of health (SBDH) play a substantial effect in a wide range of health outcomes. Electronic health records (EHRs) have been widely employed to conduct observational studies in the age of artificial intelligence (AI). However, there has been limited review into how to make the most of SBDH information from EHRs using AI approaches. Methods. A systematic search was conducted in six databases to find relevant peer-reviewed publications th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 107 publications
0
14
0
Order By: Relevance
“…This is important because there is very little research investigating disease conditions within the social environment without attention to the cost of care despite the fact that it is well known that SDOH and health conditions (and outcomes) are inextricably linked. 25 Moreover, a recent scoping review of predictive models and other data-science oriented research found that merely 20% of included studies were conducted within a social or community context. 25 Most similar to our work, Byrne and colleagues 27 have predicted housing instability and homelessness within the Veterans Health Administration using social history (e.g., branch of service, service use, and diagnosis) for personalized interventions, but their models are fit to a narrow population with a specific need, and do not take into account medical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because there is very little research investigating disease conditions within the social environment without attention to the cost of care despite the fact that it is well known that SDOH and health conditions (and outcomes) are inextricably linked. 25 Moreover, a recent scoping review of predictive models and other data-science oriented research found that merely 20% of included studies were conducted within a social or community context. 25 Most similar to our work, Byrne and colleagues 27 have predicted housing instability and homelessness within the Veterans Health Administration using social history (e.g., branch of service, service use, and diagnosis) for personalized interventions, but their models are fit to a narrow population with a specific need, and do not take into account medical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in our review applied AI to analyze large volumes of data to help elucidate the social determinants of cancer outcomes. The identification of social determinants of health can help support more comprehensive strategies to improve health equity in underserved populations [ 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…low socioeconomic status, experience significant baseline health disparities. Those pre-existing biases have the potential to be perpetuated by machine learning algorithms, reinforcing deeply rooted stigma and discrimination [86].…”
Section: Algorithmic Biasmentioning
confidence: 99%